If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -15(x + -1) = 2(6 + -3x) Reorder the terms: 4x + -15(-1 + x) = 2(6 + -3x) 4x + (-1 * -15 + x * -15) = 2(6 + -3x) 4x + (15 + -15x) = 2(6 + -3x) Reorder the terms: 15 + 4x + -15x = 2(6 + -3x) Combine like terms: 4x + -15x = -11x 15 + -11x = 2(6 + -3x) 15 + -11x = (6 * 2 + -3x * 2) 15 + -11x = (12 + -6x) Solving 15 + -11x = 12 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 15 + -11x + 6x = 12 + -6x + 6x Combine like terms: -11x + 6x = -5x 15 + -5x = 12 + -6x + 6x Combine like terms: -6x + 6x = 0 15 + -5x = 12 + 0 15 + -5x = 12 Add '-15' to each side of the equation. 15 + -15 + -5x = 12 + -15 Combine like terms: 15 + -15 = 0 0 + -5x = 12 + -15 -5x = 12 + -15 Combine like terms: 12 + -15 = -3 -5x = -3 Divide each side by '-5'. x = 0.6 Simplifying x = 0.6
| s^4+6s^2+8=0 | | 3r(7r)= | | 5a+8=2a+7 | | 10/7*3 | | -3(-x+1)=11-9x | | 12(10m+8)(6m+4)(2m)=0 | | 3y-10+y+60=8y+50-6y | | 9m+2m= | | 2(y+5)-3=4y-9-6y | | 8-8n+5n=9-58 | | 2y-6+3y=4 | | -4(3p+3)-18=3(2p+8) | | 45q+63= | | 3x+3y-9z=9 | | 1.6y=0.4y | | 5(x-4)=-4x+25 | | -52+21y+6=6(4y-3)-7 | | 25+15r= | | 3x+3=13+x | | 2(x+18)=-4(x-12) | | -6=3(y+1) | | 153=7x+5x+9 | | 3x+4=3x+8-2x+x | | 15=6y+3w | | 6x-2y=36 | | 1+3x+2x=31 | | 3x+1-4x=8 | | 3x-13=x+9 | | 14=5x-2x+2 | | 5x(x+2)-1=19 | | 7m+n-18+20n= | | (2x-4)=2 |